The Biophysical Modelling of the Time-function - Vincze, Janos; Tiszay, Gabriella Vincze- (Jour Med Resh and Health Sci, 2023)
This claim is supported by the fact that life expectancy of around 100 years has not changed since the historical record. What has changed is the number of people who are approaching or reaching this apparent limit, but without human life being extended. From a biological point of view, every living organism has a dual purpose: its own survival and the reproduction of the species. Given that life expectancy at birth was generally below 40 years in all countries before 1900, the ageing period was usually closely linked to reproduction. The functional, physiological changes that occur during ageing have also long been recognised. The ontogenetic development of an individual is nothing more than the playback of a "prewritten program", spread out over time. The process of ageing is thus included in the programme, without its beginning and end being clearly defined. The period of ageing is very often accompanied by various pathological changes, in other words, most diseases are much more likely to occur at an older age than before. Given that ageing is the last stage of post-embryonic development, it is likely to be dominated by minor or major pathological processes. Ageing does not start in the whole body at the same time. It is well known that, for example, the atrophy of the thymus gland in humans begins as early as 13–15 years of age, and that of the gonads in women between 45–52 years of age, while in contrast, certain areas of the pituitary gland show high levels of activity until late adulthood. It can be observed that the rate at which several age-related changes unfold is not significant in old age, but earlier in life.